Quality Assessment of Treated Reverse Osmosis Drinking Water in a Specific Pathogen Free Rodent Barrier (Journal of Laboratory Animal Science, 2025)
This study investigated the quality of treated reverse osmosis drinking water in a specific pathogen free rodent facility. The  water bottles placed in the animal rooms were evaluated on days 10, 14, and 21 for room-level assessment. For cage-level  assessment, the water was stored for 14 days inside the room and then evaluated on days 2 and 5 (group A – 5 mice) and  days 2, 5, 7, 9, and 14 (group B – 2 mice) after provision to the mice in individually ventilated cages. At the room level,  a significant decrease in free chlorine was observed from days 10 to 21 (p
Keywords: Drinking water; Heterotrophic bacteria; Pseudomonas; aeruginosa; Reverse osmosis; Water quality